Integration of rural landscape characters of the Pahang-Terengganu coastal route for tourism route planning - Zulkifli, Nabilah Huda; Ibrahim, Putri Haryati; Zakariya, Khalilah (Universiti Putra Malaysia, 2020)
Landscape characters of a place are shaped by its natural geographic conditions and alterations from human activities. The sceneries found along a certain route can signify the image of a place and enhance tourist experience. This study addresses issues regarding the fragmentation and disconnection of landscape characters that have potentials to be planned and integrated, so that a practical approach can be used by relevant authorities to plan the tourism route and sustain the rural landscape characters. The aim of this paper is to delineate the coastal landscapes characters along the Pahang-Terengganu east coast route. The methods used for this research are content analysis from various literature reviews to derive at a conceptual framework, field observations and assessment of the landscape characters found along the Pahang-Terengganu east coast route, and describing the landscape characters from aspects of natural factors and cultural social factors. The findings of the study revealed that the coastal landscape characters for the Pahang-Terengganu stretch are highly influenced by human interactions with the natural resources that are native to the area. The dominant landscape characters that are visible along the routes are composed of natural and cultural settings such as vegetated areas, the seaside and traditional villages, as well as industrial and commercial areas. Future plans and developments need to integrate the natural and cultural landscape characters of the route, towards establishing the Pahang-Terengganu coastal route as one of the scenic tourism routes in Malaysia.